Identification in additive error models with discrete endogenous variables - Andrew Chesher (Centre for Microdata Methods and Practice (cemmap), 2004)
In additive error models with a discrete endogenous variable identification cannot be achieved under a marginal covariation condition when the support of instruments is sparse relative to the support of the endogenous variable.
Keywords: 330; Fehlerkorrekturmodell